Digital Marketing’s Big Potential on Tiktok Platform: Users, Audiences, And Social Media Competitions - Karunia, Putra; Dewi Rahmawati Cahyaningrum; Erna Apriani (Sumber Belajar Sejahtera, 2025)
This Research aims to know the enormous potential of digital marketing on the TikTok platform, which is now growing as one of the most popular with a high amount of users and audiences, understand the characteristics of the users, and evaluate the other social media competitors. This Research used a quantitative approach with a survey to get data from 100 TikTok users, which included variables such as users, audiences, and social media competitions. Data were collected through an online questionnaire and analyzed with SmartPLS. Various generations have a strong interest in TikTok; Tiktok has a strong appeal to multiple generations, with short, interactive video content and a personalization algorithm that is effective in increasing user engagement. TikTok is also able to attract brands with more targeted marketing potential. By focusing on creativity and virality of content, TikTok competes with other platforms such as Instagram, YouTube, and X. This Research implies that TiResearch is the most effective platform for innovative digital marketing campaigns targeting a broad audience. The results show that the audience is important in increasing marketing effectiveness. On the other hand, the user variable shows a very significant influence on digital marketing effectiveness. In addition, the level of competition between social media platforms also affects the success of TikTok's digital